Classical and Novel Lipid-Lowering Therapies for Diabetic Patients with Established Coronary Artery Disease or High Risk of Coronary Artery Disease-A Narrative Clinical Review - Nikolaos Velidakis; Panagiotis Stachteas; Evangelia Gkougkoudi; Christodoulos Papadopoulos; Nikolaos P. E. Kadoglou (MDPI AG, 2024)
Diabetic atherosclerosis is a complex process that is characterized by diffuse and unstable lesions increasing 2-4-fold the risk of adverse cardiovascular (CV) events. Diabetic dyslipidemia has a predominant role in coronary artery disease (CAD) and has been the target of classical and emerging pharmaceutical agents with established or promising CV benefits. The aim of the present narrative review was to summarize the effects of classical and novel lipid-lowering pharmaceutical agents on lipid profile and CV outcomes in diabetic patients with established CAD or high risk of CAD. Statins remain the first-line treatment for all diabetic patients since they considerably ameliorate lipid parameters and non-lipid CV risk factors, leading to reduced CV morbidity and mortality. Complementary to statins, ezetimibe exerts lipid-lowering properties with modest but significant reductions in major adverse cardiovascular events (MACEs) and CV mortality. PCSK9 inhibitors considerably reduce LDL-C levels and lower MACEs in diabetic patients. On the other hand, fibrates may confer a very modest decline in MACE incidence, while the CV impact of omega-3 fatty acids is promising but remains questionable. Bempedoic acid and inclisiran have a potential therapeutic role in the management of diabetic dyslipidemia, but this is still not adequately documented. Given the heightened CV risk among individuals with diabetes, more decisive results would be of great importance in the utility of all these drugs.